2011
DOI: 10.1002/jor.21562
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve deformation in differential finger motions: Ultrasonographic comparison of carpal tunnel syndrome patients and healthy controls

Abstract: PURPOSE We investigated the median nerve deformation in the carpal tunnel in patients with carpal tunnel syndrome and controls during thumb, index finger, middle finger and a four finger motion, using ultrasound. METHODS Both wrists of 29 asymptomatic volunteers and 29 patients with idiopathic carpal tunnel syndrome were evaluated by ultrasound. Cross-sectional images during motion from full extension to flexion were recorded. Median nerve cross-sectional area, perimeter, aspect ratio of the minimal enclosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 13 publications
4
47
3
1
Order By: Relevance
“…These percentages were higher in previous studies such as Chen et al and van Doesburg et al [14][15][16][17]. This difference might be due to the use of different instruments or methods.…”
Section: Discussion ____________________________mentioning
confidence: 52%
See 1 more Smart Citation
“…These percentages were higher in previous studies such as Chen et al and van Doesburg et al [14][15][16][17]. This difference might be due to the use of different instruments or methods.…”
Section: Discussion ____________________________mentioning
confidence: 52%
“…This difference might be due to the use of different instruments or methods. Although electrodiagnostic tests are accurate and the gold standard for diagnosing carpal tunnel syndrome, 10% to 25% of cases would be missed using this test, depending on disease severity or method of performance [17]. Yesildag et al demonstrated that a median nerve circumference of more than 10.5 mm is sensitive (89%) and specific (94.7%) for CTS [6].…”
Section: Discussion ____________________________mentioning
confidence: 99%
“…In a previous study, 8 it was suggested that the deformation indices of the area, perimeter, and circularity could be used to distinguish the CTS patients from the controls. In this study, the perimeter and circularity were consistent with the results of the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…7 It was suggested that several ultrasound indices can be used to estimate the condition of the disease. 8 Using this technique, we assessed the potential of ultrasound indices to determine the severity of CTS. The objective of this study was to compare the median nerve ultrasonographic indices of CTS patients and healthy controls, and to assess the potential correlation between median nerve deformation indices and the clinical severity of CTS.…”
Section: Introductionmentioning
confidence: 99%
“…Active gliding of the extrinsic finger flexors is known to cause compression stress and deformation of the median nerve at carpal tunnel region. [2] Both flexor digitorum superficialis and flexor digitorum profundus contribute to the flexion of interphalangeal joints (IPJ) and metacarpophalangeal joint (MCPJ). Moreover, intrinsic hand muscles such as lumbricals are considered as the main contributor to the flexion of the MCPJ.…”
Section: Introductionmentioning
confidence: 99%